Combining dehydration, construct optimization and improved data collection to solve the crystal structure of a CRM1–RanGTP–SPN1–Nup214 quaternary nuclear export complex. Issue 12 (1st December 2015) - Monecke, Thomas; Dickmanns, Achim; Weiss, Manfred S.; Port, Sarah A.; Kehlenbach, Ralph H.; Ficner, Ralf
Abstract : High conformational flexibility is an intrinsic and indispensable property of nuclear transport receptors, which makes crystallization and structure determination of macromolecular complexes containing exportins or importins particularly challenging. Here, the crystallization and structure determination of a quaternary nuclear export complex consisting of the exportin CRM1, the small GTPase Ran in its GTP‐bound form, the export cargo SPN1 and an FG repeat‐containing fragment of the nuclear pore complex component nucleoporin Nup214 fused to maltose‐binding protein is reported. Optimization of constructs, seeding and the development of a sophisticated protocol including successive PEG‐mediated crystal dehydration as well as additional post‐mounting steps were essential to obtain well diffracting crystals.